A combined methodology based on Z-fuzzy numbers for sustainability assessment of hydrogen energy storage systems - Ilbahar, Esra; Colak, Murat; Karasan, Ali; Kaya, Ihsan (PERGAMON-ELSEVIER SCIENCE LTD, 2022)
One of the most significant ways of providing supply security in energy and effective utilization of energy sources is energy storage. Hydrogen, which is a crucial energy carrier, has received more attention in recent years due to its importance for a carbon-free economy and society. There are various physical and material-based storage methods for hydrogen storage. When examined in terms of factors that may affect the storage decision, each storage alternative has positive and negative features. In this regard, determining the most suitable hydrogen energy storage alternative by considering economic, technological, environmental, and social factors is a decision-making problem which is needed to be handled carefully to benefit from this technology in the most effective way. Since this problem requires the consideration of many criteria, some of which have dependencies among themselves or conflict with each other, and experts' judgments including uncertainty along with different degrees of reliability, a multi-criteria decision making (MCDM) approach based on z-fuzzy numbers will be an appropriate tool to make an efficient investment decision. Through that, in this study, a novel combined methodology consisting of Decision-MAking Trial and Evaluation Laboratory (DEMATEL), cognitive mapping, and VIseKriterijumska Optimizacija I Kompromisno Resenje (VIKOR) methods under z-fuzzy environment has been introduced. In the study, after the proposed z-fuzzy DEMATEL method is used to identify the dependencies among energy storage technologies' assessment criteria, z-fuzzy cognitive mapping is employed to determine the importance degrees of criteria. Finally, the most suitable hydrogen energy storage alternative is selected by utilizing the z-fuzzy VIKOR technique. As a result of applying this methodology, storage capacity and response time have been determined as the most and the least important criteria with the weights of 0.0649 and 0.0447 respectively, and the alternative carbon nanotubes has been determined as the most appropriate option for Turkey. Comparative and sensitivity analyses have also been carried out to validate the proposed methodology and demonstrate the flexibility and robustness of decisions. As a result, we aimed to present a beneficial road map for researchers and policymakers studying hydrogen storage. (c) 2022 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Hydrogen; Energy storage; Fuzzy set theory; MCDM; Z-Numbers; MULTICRITERIA DECISION-MAKING; SITE SELECTION; VIKOR METHOD; TECHNOLOGIES; SETS; Chemistry; Electrochemistry; Energy & Fuels